2007
DOI: 10.1016/j.bbrc.2007.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Th2 cells are required for both eosinophil- and neutrophil-associated airway inflammatory responses in mice

Abstract: Most current animal models focus on eosinophil-mediated asthma, despite compelling evidence that a neutrophil-mediated disease occurs in some asthma patients. Using intranasal challenge of mice sensitized either orally or nasally with whole peanut protein extract in the presence of cholera toxin, we developed mouse models of eosinophil-and neutrophil-mediated asthma, respectively. In this study, mice deficient in Th1 (IL-12 and IFN-γ) or Th2 (IL-4 and IL-13) pathways were used to characterized the role played … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In this context, we were most surprised to observe that Ag-specific IgG levels (total, IgG1 and IgG2a) were not affected in ASC Ϫ/Ϫ mice as predicted during a Th1 to Th2 shift (49,50). We currently have no explanation for this discrepancy, but such discrepancy has already been observed in other experimental situations (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 75%
“…In this context, we were most surprised to observe that Ag-specific IgG levels (total, IgG1 and IgG2a) were not affected in ASC Ϫ/Ϫ mice as predicted during a Th1 to Th2 shift (49,50). We currently have no explanation for this discrepancy, but such discrepancy has already been observed in other experimental situations (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 75%
“…[25][26][27][28][29] However, few studies in human subjects and mice have reported on the positive contribution of T H 1 lymphocytes and IFN-g to allergic lung inflammation. [30][31][32][33] These discrepancies might be in part attributed, as pointed out by some of these authors, to differences in experimental models (dose, timing, and means of IFN-g or anti-IFN-g administration; use of IFN-g-or IFN-g receptor-deficient animals and genetic background) but might also reflect a dual role for IFN-g, as recently suggested for autoimmune diseases. 34 Nevertheless, the positive or negative effects observed on airway inflammation were considered to target or arise from lymphocytes.…”
Section: Discussionmentioning
confidence: 85%
“…By using knockout model mice for IFNG or IL4 and/or IL13 genes, it was also shown that both T H 1 and T H 2 cells were required for both eosinophiland neutrophil-associated airway inflammation. 25 Evidence for CXCR3's functions in atopic responses of asthma has also been found. Thomas et al 26 suggested that CXCR3 plays a role in inflammatory T-cell recruitment to the bronchoalveoli during the allergic inflammatory response by using an endobronchial segmental allergen challenge in human atopic asthmatic subjects.…”
Section: Discussionmentioning
confidence: 93%